2011
DOI: 10.1007/s11250-011-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence for brucellosis in Bos indicus in Nigeria

Abstract: The results indicate that bovine brucellosis is an important veterinarian problem in Nigeria. The easy-to-use and robust field test is most promising for field-based surveillance as it provides an immediate result allowing the prompt instigation of control measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Indicating that infection of brucellosis is dependent on breed (P<0.05). Bertu et al (2011) found out that, in the Benue state in Nigeria, Red Fulani breed recorded 11.1% serprevalence against 10.4% for the White Fulani. In another study using the Red Fulani and the Bunaji breed, Cadmus et al (2008) found that the Red Fulani breed had the most positive reaction.…”
Section: Effect Of Breed Distribution On Brucella Infection In Cattlementioning
confidence: 91%
See 2 more Smart Citations
“…Indicating that infection of brucellosis is dependent on breed (P<0.05). Bertu et al (2011) found out that, in the Benue state in Nigeria, Red Fulani breed recorded 11.1% serprevalence against 10.4% for the White Fulani. In another study using the Red Fulani and the Bunaji breed, Cadmus et al (2008) found that the Red Fulani breed had the most positive reaction.…”
Section: Effect Of Breed Distribution On Brucella Infection In Cattlementioning
confidence: 91%
“…The vulnerability is more pronounced with dairy production units which have developed around rapidly growing urban centres. The disease is present throughout the African continent (Chimana et al, 2010;Matope et al 2011;Megersa et al, 2011) and has also been reported in two of Cameroon's neighboring countries, Nigeria and Chad (Bertu et al, 2011;Schelling et al, 2003).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, contemporary assessments indicate a lower prevalence than that presented by Akakpo. Serological evidence of its existence has been demonstrated in many studies in sub-Saharan countries like Côte d'Ivoire (Sanogo et al 2013), Uganda (Kashiwazaki et al 2012), Ethiopia (Asmare et al 2013), and Togo (Dean et al 2013), and in particular some neighboring countries to Chad, notably from the southwest where the study area borders Nigeria (Alausa et al 1976, Bertu et al 2012, Mai et al 2012.…”
Section: Brucellosismentioning
confidence: 97%
“…Recent investigations based on serological studies have shown that bovine brucellosis is endemic in Nigeria (Abdou 2000;Ate et al 2007;Cadmus et al 2010) and that there is an apparent increase in its occurrence in the country (Junaidu, Oboegbulem & Salihu 2011;Ocholi et al 2004). Previous reports have indicated that the prevalence of bovine brucellosis may be influenced by herding different species together (Bale, Nuru & Addo 1982;Junaidu, Oboegbulem & Salihu 2008;Ocholi et al 2004), use of common pastures and water sources (Bertu et al 2012), age (Cadmus, Adesokan & Stack 2008;Junaidu et al 2011;Ocholi et al 1996), breed (Cadmus et al 2008;Esuruoso 1974), sex (Atsanda & Agbede 2001;Junaidu et al 2011), lactation status (Junaidu et al 2011) and season (Bertu et al 2012;Nuru & Dennis 1976). However, the role of different cattle production systems needs to be assessed given the uncontrolled free movement of animals, especially as practised by the Fulani herdsmen, and unsupervised introduction of new animals into herds.…”
Section: Introductionmentioning
confidence: 99%